(untitled) (International Journal of Engineering and Computer Science, 2017)
Intrusion Detection Systems are designed to monitor a network environment and generate alerts whenever abnormal activities are detected. However, the number of these alerts can be very large making their evaluation a difficult task for a security analyst. Alert management techniques reduce alert volume significantly and potentially improve detection performance of an Intrusion Detection System. To Improve the effectiveness and efficiency of an Intrusion Detection System by significantly reducing the false positive alerts and increasing the ability. Proposed technique addresses the issues relating the optimality of decision-making through correlation in multiple sensors framework. The process is based on through Dempster Shafer rule. Moreover, the reliability factor for any Intrusion Detection System is also addressed accordingly in order to minimize the chance of false diagnose of the final network state. A considerable number of simulations are conducted in order to determine the optimal performance of the proposed prototype. In this paper we are introduce combines evidence from two homogenous and one heterogeneous ids using dempster-shafer algorithm